LINGKUNGAN BELAJAR ABAD 21 PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DI SEKOLAH DASAR NEGERI (SDN) 3 TAPA, KABUPATEN BONE BOLANGO - Mokoginta, Desita; Pomalingo, Samsi; Ismail, Reska Putri (SINERGI : Jurnal Riset Ilmiah, 2025)
This study elaborates the concept of 21st century learning environment applied in Civics learning in Elementary Schools, learning strategies used in 21st century learning environment in Civics learning in Elementary Schools, and the impact of implementing 21st century learning environment on students’ motivation, learning outcomes, and character in Civics learning? This study aims to analyze the implementation of 21st century learning environment culture in Civics learning in Elementary School 3 Tapa, Bone Bolango Regency. This study focuses on three main aspects: the concept of 21st century learning environment applied, learning strategies used, and its impact on students’ motivation, learning outcomes, and character. The research method used is qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of educational technology, such as the use of applications and social media, significantly increases student engagement in the learning process. Various learning strategies, such as project-based learning and collaborative methods, successfully create an interactive and enjoyable learning atmosphere, which encourages students to actively participate. The positive impact of implementing this 21st century learning environment is seen in the increase in students’ learning motivation and academic outcomes, as well as the development of better civic character. This study recommends the need for additional training for teachers to utilize technology and innovative learning methods in improving the quality of education in the modern era.